2019
DOI: 10.15171/jlms.2019.s4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the SRC Inhibition Role in the Efficacy of Breast Cancer Radiotherapy

Abstract: Introduction: Radiotherapy (RT) is an effective therapeutic method for preventing the recurrence of breast cancer after surgery. The development and improvement of RT are of interest to scientists. Possible improvement of RT via study of dysregulated proteins of breast cancer cell line MDA-MB-231 which is exposed to 10 Gray (Gy) radiation is aim of this study. Methods: Using protein-protein interaction (PPI) network analysis by means of running Cytoscape software via the STRING database, the up-regulated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the interaction between EOC and the mesothelial cells is critical for the formation of peritoneal metastasis [23]. It is at this point that the primary mesothelial cells express FN1, which binds to the extracellular domain of CSPG4 [24]. Previous studies have revealed that the TGF-β secreted by EOC cells in malignant ascites alters the conditions of the mesothelial cells [20,25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the interaction between EOC and the mesothelial cells is critical for the formation of peritoneal metastasis [23]. It is at this point that the primary mesothelial cells express FN1, which binds to the extracellular domain of CSPG4 [24]. Previous studies have revealed that the TGF-β secreted by EOC cells in malignant ascites alters the conditions of the mesothelial cells [20,25].…”
Section: Discussionmentioning
confidence: 99%
“…GSN is an actin binding protein, a key regulator of actin filament assembly and disassembly, and is involved in cell movement, shape, and metabolism (Feldt et al, 2019). Studies have shown that GSN gene transcription is down-regulated in breast cancer of humans and some animals, and the activation of GSN may be a protective factor in the treatment of cancer cells against cancer (Mielnicki et al, 1999;Shahrokh et al, 2019). The secreted GSN inhibits the invasion and migration of colon cancer cells (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%